Simulation on Air-Fly Ash Particles Using Discrete Phase Method - Zahari N.M.; Harun M.F.; Zainoodin M.; Mohamad D.; Syamsir A.; Ramli. M.Z.; Zawawi M.H.; Abas A. (IOP Publishing Ltd, 2023)
In order to suggest for development of a better fluidized bed combustor designs, numerical simulations could be used to model the flow behavior inside the boilers. However, the complex nature of the multiphase flow of particles and combustion air makes the modelling very challenging. In this study the relatively recently introduced approaches for fly ash particles distribution model in CFD setting are studied. The applicability of the approaches is examined, and the computational requirements of the approaches are compared. Euler-Lagrange approach is used in order to track the particles in the simulation. The simulations results obtained are compared between different shape of simple models, square and cylindrical. Published under licence by IOP Publishing Ltd.